Study of secondary neutron interactions with 232Th, 129I, and 127I nuclei with the uranium assembly "QUINTA" at 2, 4, and 8 GeV deuteron beams of the JINR Nuclotron accelerator. (January 2016) - Adam, J.; Chilap, V.V.; Furman, V.I.; Kadykov, M.G.; Khushvaktov, J.; Pronskikh, V.S.; Solnyshkin, A.A.; Stegailov, V.I.; Suchopar, M.; Tsoupko-Sitnikov, V.M.; Tyutyunnikov, S.I.; Vrzalova, J.; et al.
Abstract: The natural uranium assembly, "QUINTA", was irradiated with 2, 4, and 8 GeV deuterons. The 232 Th, 127 I, and 129 I samples have been exposed to secondary neutrons produced in the assembly at a 20-cm radial distance from the deuteron beam axis. The spectra of gamma rays emitted by the activated 232 Th, 127 I, and 129 I samples have been analyzed and several tens of product nuclei have been identified. For each of those products, neutron-induced reaction rates have been determined. The transmutation power for the 129 I samples is estimated. Experimental results were compared to those calculated with well-known stochastic and deterministic codes. Highlights: The natural uranium assembly, "QUINTA", was irradiated with 2, 4, and 8 GeV deuterons. The 232 Th, 127 I, and 129 I samples have been exposed to secondary neutrons produced in the assembly at a 20-cm radial distance from the deuteron beam axis. The spectra of gamma rays emitted by the activated 232 Th, 127 I, and 129 I samples have been analyzed and several tens of product nuclei have been identified. For each of those products, neutron-induced reaction rates have been determined. The transmutation power for the 129 I samples is estimated. Experimental results were compared to those calculated with well-known stochastic and deterministic codes.